Penyederhanaan Informasi Nilai Gizi Pangan Olahan Menggunakan Indeks Nutrient-Rich Foods - Yogi Karsono; Nurheni Sri Palupi; Dede Robiatul Adawiyah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2021)
Healthy diet is an effort to reduce the risk of non-communicable diseases (NCDs). The use of scientific terms on nutrition information panels (NIP) is complicated and difficult to understand, so that it becomes an obstacle in delivering accurate nutritional information for consumers. Nutrients-Rich Foods (NRFn,3) Index provides an alternative to simplify NIP. In general, nutrient-rich foods are asso-ciated with high-priced products. This study aimed to analyze correlation between NRFn,3 index with nutrients fulfillment and price of products. NIP of dairy products and their analogues were used as research samples. The NRFn,3 index was determined using two calculation bases, 100 kcal and 100 g of ready-to-consume products. NRF12,3 index score in ready-to-drink (RTD) milk and instant powdered milk positively correlated with the fulfillment of 11 nutrients to encourage. The average NRF12,3 index score per 100 g of instant powdered milk was 91, higher than RTD milk which was only 76. As nutrient-dense foods, they had an index score of NRF12,3 per 100 kcal that was higher per 100 g. Products with higher NRF12,3 index scores tended to be marketed at higher price than that of lower ones.